Analisis Serat Kasar Produk Snack Bar Berbasis Tepung Kacang Gude (Cajanus Cajan), Dengan Kacang Kratok (Phaseolus Lunatus) Dan Kacang Merah (Phaseolus Vulgaris) - Ida Ayu Putu Ary Widnyani; I Gusti Agung Yogi Rabani RS; Putu Rima Sintyadewi (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2021)
The dense activity and mobility of modern society often results in them consuming foods high in energy but with minimal fiber content. Lack of fiber consumption will affect our digestive system disorders. By utilizing local materials in snack bar products, it is expected to contribute to improving the food security and independence program. The purpose of this research is to analyze crude fiber components of the product. This reaserch used randomized block design factorial with 8 tratments and 2 replications. The treatments were comparison between Cajanus cajan flour : Phaseolus lunatus and Phaseolus vulgaris nuts (1:4, 1:6, 1:8, 1:1, 3:4, 3:6, 3:8, 3:10). The result showned that treatments of the reasearch have a very significant effect to the crude fiber content (P>0,01). The highest crude fiber content is 14,66% (3:10) and the lowest is 11,11% (1:4).